Fetal Malnutrition and Associated Factors among Term Newborn Babies at Birth in South Gondar Zone Hospitals, Northwest Ethiopia - Desalegn Tesfa; Fentaw Teshome; Birhanie Ambaw (Hindawi Limited, 2021)
Background. Undernutrition contributes to almost half of all under-five deaths. Fetal malnutrition (FM) has been implicated in both short- and long-term consequences among fetal, neonatal, and adult life. Currently, Ethiopia lacks information on the prevalence of fetal malnutrition and its associated factors. This study, therefore, is aimed at assessing the prevalence of FM at birth and its associated factors in South Gondar zone hospitals, northwest Ethiopia. Methods. A cross-sectional study was carried out from November 1, 2019, to April 30, 2020, among four hospitals of South Gondar zone. All women with their live newborns who met the eligibility criteria were included. Clinical assessment of nutritional status including other anthropometric measurements was done immediately after delivery. The newborn was declared as fetal malnourished if the clinical assessment of nutritional status cut-off point is less than 25. Data were collected by trained clinical midwives. Besides bivariate regression analysis, a multivariable logistic regression analysis was done to identify associations. Results. A total of 1592 mothers with their live newborns participated in this study. The prevalence of fetal malnutrition was 21.7% (95% CI: 19.7-23.9). Intimate partner violence (AOR: 1.97, 95% CI: 1.52-2.56), placental weight less than 512 grams (AOR: 2.76, 95% CI: 2.13-3.57), and small for gestational age (AOR: 1.96, 95% CI: 1.46-2.62) were significantly associated with fetal malnutrition. Conclusions. The prevalence of fetal malnutrition was a public health problem in this study. Intimate partner violence, placental weight, and small for gestational age were found the most significant variables. To avert fetal malnutrition, positive family relation and additional or balanced nutritional supplementation during pregnancy are critical. We recommend researchers do clinical follow-up research which comprises a detailed investigation of placental, maternal, and fetal factors including genes.